The Role of University in Achieving Sustainable Development Goals of Sripatum University in Thailand. - Chairattanawan, Kanidta; Thapsut, Monnapa (Nimitmai Review Journal, 2024)
Universities are increasingly engaging with the Sustainable Development Goals (SDGs). As well as Sripatum University, because SDGs are seen as enablers of societal transformations and transformations within universities. This research article aims to study the situation of Sripatum University in SDGs and to establish a policy to support sustainable development goals. We use qualitative methods, utilizing a literature review, structured observation and comprehensive in -depth interviews. There are five key informants which was selected by purposive sampling, 16 participants, including students, academics (lecturers), sustainability coordinators, executives and support services. The instrument for this research was guideline for interview, Data was analyzed by content analysis. This study shows that the president has appointed a working group to drive the sustainable development goals. During the academic year 2022-2023, Sripatum University focuses on 6 groups of SDGs, including SDG 4: Quality Education, SDG-5: Gender Equality, SDG-7: Affordable and Renewable Energy, SDG-9: Innovation and Infrastructure, SDG-16: Peace and Justice and strong institutions, and SDG-17: Partnerships for the Goals. But knowledge, understanding and awareness in SDGs in staff and students are so little. Whereas everyone has continued to carry out activities or projects linked to the SDGs. However, they do not understand the relevance or relationship in the SDGs. Five strategies of the Sripatum University to encourage faster achievement of the targeted SDGs are proposed are as follows: Curriculum Integration, Research and Innovation, Community Engagement, Partnerships and Collaboration and Communication.